Autoantibody Diagnostics in Neuroimmunology: Experience From the 2018 Italian Neuroimmunology Association External Quality Assessment Program - Gastaldi, Matteo; Zardini, Elisabetta; Scaranzin, Silvia; Uccelli, Antonio; Andreetta, Francesca; Baggi, Fulvio; Franciotta, Diego (Frontiers in Neurology, 2020)
Background Both clinical and laboratory neuroimmunology has impressively expanded in the past decades. The introduction of novel assays such as cell-based assays (CBAs), which make antigens be expressed in their native conformation and recognized by conformational antibodies (Abs), has improved the diagnostics, but introduced demanding laboratory tasks too. In this scenario, test standardization and quality controls represents a key step to promote accuracy. We critically report on the results of the 2018 external quality assessment program (EQAP) organized by the Italian Neuroimmunology Association . Methods EQAP regarded 10 schemes, including oligoclonal bands (OCBs), intracellular neuronal (ICN) Abs, neuronal surface (NS) Abs, aquaporin-4 (AQP4) Abs, myelin oligodendrocyte glycoprotein (MOG) Abs, myelin-associated glycoprotein (MAG) Abs, ganglioside Abs, acetylcholine-receptor (AChR) Abs, and muscle-specific-kinase (MuSK) Abs, and 34 laboratories. Assays were classified as tissue-based assays (TBAs), solid-phase assays (SPAs), liquid-phase assays (LPAs), and CBAs. Twenty-four samples were provided. Results Median accuracy for the laboratories was 75% (range, 50-100). In 8/10 schemes, at least one sample provided discrepant results. Inter-laboratory ‘substantial agreement’ was found in 6/10 schemes (AChR, MuSK, MAG, AQP4, MOG, and NS Abs), whereas the worst agreement regarded OCBs and ganglioside Abs. Three-quarter of the tests were commercial. Both commercial and in-house assays seemed to perform better in experienced laboratories. Conclusions This real-life snapshot of the neuroimmunology test performances highlights shortcomings attributable to factors including technician-dependent suboptimal performances, structural limitations inherent to assays(such as isoelectric focusing for OCBs and SPAs for ganglioside Ab detection) and errors in test interpretations.